MODERN DIAGNOSTIC METHODS FOR IRON DEFICIENCY ANEMIA: FROM CLINICAL PRACTICE TO MOLECULAR RESEARCH (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Iron deficiency anemia (IDA) is one of the most common forms of anemia worldwide. This article explores modern diagnostic methods for IDA, ranging from standard laboratory analyses to molecular research. The importance of integrating various diagnostic approaches to enhance diagnostic accuracy is emphasized.